CURRENT PROBLEMS AND PROSPECTS FOR THE DEVELOPMENT OF LEGAL REGULATION OF PUBLIC CIVIL SERVICE IN THE JUDICIARY - MARTIROSYAN PAILAK (Legal Bulletin)
The relevance of the issues discussed in the article is due to the need to create and improve the institution of the state judicial service, which is associated with a number of significant and increasingly obvious problems arising in the field of legal regulation of judicial authorities in Russia. First of all, it should be noted that currently court staff at all levels have the status of government civil servants, which, of course, is related to their official legal status and responsibilities. However, the activities of these officials are unique, as they not only ensure the normal functioning of the judiciary, but also play a key role in the administration of justice, the execution of court decisions, as well as in ensuring other powers assigned to the courts. It is important to emphasize that their activities are directly related to the functioning of the judiciary as an institution that plays a central role in the system of separation of powers in Russia. This raises the question of the need to separate judicial officers into a separate category of employees, different from the general mass of State civil servants working in executive authorities. The main purpose is to study current problems and prospects for the development of legal regulation of the civil service in the judiciary. The problems under consideration are: the separation of the judicial service as a separate type of public service; the introduction of the practice of having two or three judicial assistants for one judge. Methods used: analysis, synthesis, formal legal method, comparative legal. Conclusions: the need to create a state judicial service; the introduction of the practice of having two or three judicial assistants for one judge; providing judicial assistants with separate functions for the administration of justice.